Structural basis for selective recognition of acyl chains by the membrane-associated acyltransferase PatA - David Albesa-Jové (Nature Portfolio, 2016)
PatA is a membrane-associated acyltransferase that is essential for the biosynthesis of mycobacterial glycolipids. Here, Albesa-Jovéet al. describe structures of PatA from Mycobacterium smegmatisin complex with acyl donors and show that catalysis occurs by an unusual charge-relay mechanism.